MONITORING OF THE METAL STRUCTURAL STATE BY ACOUSTICAL STRUCTURAL NOISE - V. V. Muraviev; O. V. Muravieva; A. I. Dedov; A. V. Baiteryakov (Приборы и методы измерений, 2015)
To determine the structural state of the metal as an informative parameter the structural acoustic noise is proposed. The paper represents the experimental results of the use at acoustical structural noise for the determination at the structural state of carbon pipe steels exposed by heat treatment, corrosion and tensile loads. The effect of grain size, corrosion and tensile loads on the level of structural noise is discussed.